Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. Science, Technology, Engineering, and Mathematics (STEM) Education in the United States of America and Saudi Arabia: A Comparative StudyDr. Saud Mutlaq Al-Otaibi2. Effect of regulating proportion of track students on cognitive learning outcome of natural science courses in single-track schoolsMr. Mohammed Mufarrih Al-Shahrani3. The effectiveness of a training program in improving human quality among a sample of female students at Qatar UniversityProf. Musalam Salim Ali Al-Waheibi4. Employing the Short Story with Pictures to Enhance the Language Development of Deaf and Hard of Hearing Students from the Point of view of their teachersMrs. Hessa Saleh Waqit Al-Zahrani, Dr. Omar Fawwaz Abdelaziz5. The degree of use of the Ain educational portal in distance education and the obstacles and requirements of use from the point of view of teachers and primary school principals  in the city of AbhaMrs. Manal Ali Al Saad Al-Qahtani6. Employing Alternative Assessment Strategies and Their Obstacles from The Perspective of Arabic Language Teachers at the Secondary School LevelMrs. Wafa'a Hamed Muda Al-Alawi , Dr. Khdijah Mohamad Omar Haji7. Academic Self-Efficacy and its relation to Academic Boredom among Umm Al-Qura University female studentsMrs. Makiah Abdo Hammdi
Keywords: Journal of Educational and Psychological Sciences